Gajah Purba Sebagai Ide Pengembangan Motif Batik Sragen - Hartono, Lili; Mulyanto, Mulyanto (Balai Besar Standardisasi dan Pelayanan Jasa Industri Kerajinan dan Batik, 2020)
ABSTRACTSragen Regency is the biggest batik producer in the Solo Raya region. Batik is one of Sragen's superior products, but the existing batik motifs do not yet reflect regional identity. For this reason, it is necessary to develop batik motifs that take the icon of the Sragen region, namely the ancient Sangiran site, specifically the shape of the elephant pubes and bones. The purpose of this study is to make batik motifs that have visual characteristics, so that they can become Sragen regional icons. This research was carried out in the Jalidin batik handicraft business, using the participatory action review method and the creativity development of the craftsmen. The objects of elephants and ancient bones studied were used as a source of ideas in developing batik motif designs by developing the creativity of craftsmen. The results of the study there are two batik motif designs that have the uniqueness and characteristics of the Sragen region, namely the rojo elephant motif and the balung elephant motif. Both of these motifs are the result of exploration and development of the shape of an ancient elephant's head, an ancient elephant consisting of bones, and stylized bone shapes. The design motif includes a design motif for clothes and a fabric motif that can also be made for clothing. The application of motif design development is done by the process of written batik with synthetic dyes and natural dyes. Keywords: motif, batik, elephant, bones